In vivo functional analysis of the Drosophila melanogaster nicotinic acetylcholine receptor Dα6 using the insecticide spinosad. (September 2015) - Somers, Jason; Nguyen, Joseph; Lumb, Chris; Batterham, Phil; Perry, Trent
Abstract: The vinegar fly, Drosophila melanogaster, has been used to identify and manipulate insecticide resistance genes. The advancement of genome engineering technology and the increasing availability of pest genome sequences has increased the predictive and diagnostic capacity of the Drosophila model. The Drosophila model can be extended to investigate the basic biology of the interaction between insecticides and the proteins they target. Recently we have developed an in vivo system that permits the expression and study of key insecticide targets, the nicotinic acetylcholine receptors (nAChRs), in controlled genetic backgrounds. Here this system is used to study the interaction between the insecticide spinosad and a nAChR subunit, Dα6. Reciprocal chimeric subunits were created from Dα6 and Dα7, a subunit that does not respond to spinosad. Using the in vivo system, the Dα6/Dα7 chimeric subunits were tested for their capacity to respond to spinosad. Only the subunits containing the C-terminal region of Dα6 were able to respond to spinosad, thus confirming the importance this region for spinosad binding. A new incompletely dominant, spinosad resistance mechanism that may evolve in pest species is also examined. First generated using chemical mutagenesis, the Dα6 P146S mutation was recreated using the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/ Cas9 system, the first use of this technology to introduce a resistant mutation into a controlled genetic background. Both alleles present with the same incompletely dominant, spinosad resistance phenotype, proving the P146S replacement to be the causal mutation. The proximity of the P146S mutation to the conserved Cys-loop indicates that it may impair the gating of the receptor. The results of this study enhance the understanding of nAChR structure:function relationships. Graphical abstract: Highlights: Expression of chimeric Dα6/Dα7 subunits confirms the role of the region beyond Dα6 V347 in spinosad binding. Characterised an incompletely dominant, spinosad resistant mutation, Dα6 P146S, which may arise in pest species. Used CRISPR to introduce the Dα6 P146S mutation into a controlled genetic background confirming that it confers resistance.